Civilization and barbarism, according to Júlio Dinis and Fialho de Almeida - Martini, Elisabeth (2022)
Faced with the true revolution that the advances in technology caused in all fields of knowledge, especially from the second half of the nineteenth century, literature channeled the hopes and anxieties that palpitated in Portuguese society, due to the overflow of scientific thought, offering glimpses of modernity that echo to our days. Trained doctors, Joaquim Guilherme Gomes Coelho (1839-1871) - eternally known by the pseudonym Júlio Dinis - and José Valentim Fialho de Almeida (1857-1911) invested in journalism and literary writing, offering counterpoints between civilization and barbarism in their fiction, which I propose to unveil.